2004
DOI: 10.1111/j.1467-842x.2004.tb00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Children of prisoners: a growing public health problem

Abstract: Objectives: To estimate the number and proportion of children in New South Wales affected by parental incarceration, and to describe the health impact of punitive incarceration on the children of prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 14 publications
1
46
1
Order By: Relevance
“…There are an estimated 60,000 children under 16 years of age in the state of New South Wales (NSW) who have experienced parental incarceration; at least one in five are Indigenous children (Quilty, Levy, Howard, Barratt, & Butler, 2004). Over the last two decades, the number of prisoners in Australia rose by 31%, which is greater than the average increase in all other countries that are members of the Organization for Economic Co-operation and Development (OECD) (ABS, 2009).…”
Section: The Australian Contextmentioning
confidence: 99%
“…There are an estimated 60,000 children under 16 years of age in the state of New South Wales (NSW) who have experienced parental incarceration; at least one in five are Indigenous children (Quilty, Levy, Howard, Barratt, & Butler, 2004). Over the last two decades, the number of prisoners in Australia rose by 31%, which is greater than the average increase in all other countries that are members of the Organization for Economic Co-operation and Development (OECD) (ABS, 2009).…”
Section: The Australian Contextmentioning
confidence: 99%
“…With well designed and delivered antenatal care and early childhood programs, along with effective interventions helping young adults to adopt healthy behaviours, there is a tremendous opportunity to temper the emergence of chronic illnesses in younger people. Research also suggests that Indigenous Australian children are more likely to experience parental incarceration than non-Indigenous children (Quilty et al 2004). Findings from measure 2.14 should be considered in the context of the broader societal consequences of exposure to the criminal justice system and the way this impacts on the health and wellbeing of families.…”
Section: Discussionmentioning
confidence: 99%
“…Borzycki and Baldry (2003) discovered 58% of over 22,000 incarcerated individuals had been previously imprisoned in Australia. Quilty et al (2004) found Indigenous Australians are highly over-represented in prisons, comprising 20% of this population and yet only 2% of the national population. Harding (1998) found that once an Indigenous Australian is arrested the likelihood of them being rearrested is 92%.…”
Section: Traumatic Grief Prisoners and Recidivismmentioning
confidence: 99%